2020
DOI: 10.1111/cag.12638
|View full text |Cite
|
Sign up to set email alerts
|

Who uses ride‐hailing? Policy implications and evidence from the Greater Toronto and Hamilton Area

Abstract: While many are eager to guide policy decisions on ride‐hailing, understanding the broader social and travel implications hinges on local contexts. Towards providing policy guidance in the Canadian context, this paper explores how mobility sub‐markets are related to ride‐hailing use in the Greater Toronto and Hamilton Area. Using data from a 2018 travel survey, cluster analysis is used to identify four traveller sub‐markets which are compared with ride‐hailing use. The first comprises “multi‐modalists,” who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(69 reference statements)
1
4
0
Order By: Relevance
“…This suggests that these trips could be understood as complementary to public transit. Similar findings were reported by Shi and Sweet (2020), in that on-demand ride-hailing is providing transportation access to low-income households and those with limited taxi and personal automobility access. Finally, Shaheen and Chan (2016) contend that on-demand ride-hailing has the potential to provide access to public transportation as a first-and last-mile transportation option.…”
Section: Literature Reviewsupporting
confidence: 84%
See 2 more Smart Citations
“…This suggests that these trips could be understood as complementary to public transit. Similar findings were reported by Shi and Sweet (2020), in that on-demand ride-hailing is providing transportation access to low-income households and those with limited taxi and personal automobility access. Finally, Shaheen and Chan (2016) contend that on-demand ride-hailing has the potential to provide access to public transportation as a first-and last-mile transportation option.…”
Section: Literature Reviewsupporting
confidence: 84%
“…2.1 On-Demand Ride-Hailing: An Overview On-demand ride-hailing is a service where an individual requests a ride in a vehicle using a mobile phone application and includes services such as those operated by Uber and Lyft (Shaheen & Chan, 2016). The nature of the vehicle, which is private and decentralized, is a defining feature of ondemand ride hailing (Shi & Sweet, 2020). Taxi services have often been characterized as the primary competitor for on-demand ride-hailing (Brail, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that despite ride-hailing being used predominantly by wealthier residents, it can also have positive impacts on equity. An analysis of survey data in the Greater Toronto Area indicated that that "low-mobility" travelers, who have lower likelihoods of being employed, have fewer cars per household, and have a high reliance on public transit, are the second largest type of ride hailing traveler after younger and highly educated travelers (Shi & Sweet, 2020) they were also negatively associated with weekend trips (Lavieri et al, 2018). In her study of ride hailing trips in Los Angeles, Brown found that while a larger portion of ride hailing users lived in high-income areas, users who lived in low-income areas made more trips (Brown, 2019).…”
Section: Ride Hailing Usersmentioning
confidence: 99%
“…Transit agencies have highlighted potential benefits while rationalizing partnerships with TNCs to provide on demand transit (Curtis et al, 2019;Feigon & Murphy, 2018;Thomas et al, 2021). Subsidized ride hailing may increase equity, combat transit poverty in low-density areas, and provide mobility options to people with lower household incomes and lower access to private vehicles (Allen & Farber, 2019;Shi & Sweet, 2020;Yan et al, 2019). On-demand services that offer door-to-door service are be especially impactful for elderly and paratransit users for whom walking to a stop can be a significant barrier to using transit (Miah et al, 2020).…”
Section: Ride Hailing As Public Transitmentioning
confidence: 99%